Development of higher order thinking skill questions using Stahl and Murphy's taxonomy on excretion system topic - Cahya Gita Camila; Afandi Afandi; Andi Besse Tenriawaru; Wiwit Artika; Nurfadilah Siregar (Assimilation: Indonesian Journal of Biology Education, 2023)
This study aims to determine the development of higher-order thinking skills questions using Stahl's and Murphy's Taxonomy on excretory system material for 8th grade of junior high school. The subjects of this study were 305 8th grade students of Junior High School 2 Sintang. This study uses the Research and Development method. The sampling technique uses total sampling. The instrument used is a multiple-choice test consisting of 50 questions on excretory system material. The results of this study based on the validity of items showed that the number of questions accepted was 50 items. Reliability analysis showed Cronbach's alpha value of 0.71, person reliability value of 0.71, and item reliability of 0.94. Through this research, we found that the instrument of higher-order thinking skills using Stahl and Murphy's taxonomy on excretion system material for 8th grade of junior high school can be said to be valid and reliable.